The Analysis of a Skeleton with Otitis Media Found in the Remains of Kelenderis Antique City - Günay, Işın; Teke, Hacer Yaşar; Bilge, Yaşar; Güleç, Erksin (The Bulletin of Legal Medicine, 2007)
Pathological conditions are important as a part of identification process in skeleton. The aim of this study, although age, sex, sex and heigh are used for identification that can be inadequate, there are alternative ways for identification process, such as bone fractures, anormalies and differences. Our case is a young adult was found in arceologic excavating in Kelenderis Antic City with M52 inventory and we investigated the lesion located in its cranium. Age estimation was done with sutura and teeth analysis. The case suffered from otitis media and it can be used in identification process, this is because this condition is difference in his society. Morover, the cause of death could be some complications, such as brain abcesses or meningitis due to untreated otitis media.Keywords: Identification, cause of death, otitis media, Kelenderis, paleopathology
Keywords: identification; cause of death; otitis media; kelenderis; paleopathology